Hank The Cowdog: The Case of the Vampire Vacuum Sweeper - Book 29 - Erickson, John R (Houston, Texas : Gulf Publishing Co, 1997)
In his own modest way, Hank the Cowdog recounts how he barely escaped crazy Slim and his tail-eating vacuum sweeper and single-handedly saved the ranch from a huge catastrophe.
Keywords: Dogs -- Fiction; Humorous Stories; West (U.S.) -- Fiction